2021
DOI: 10.3389/feart.2021.751543
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Shale Pores and Surfaces and Their Potential Effects on the Fluid Flow From Shale Formation to Fractures

Abstract: Fluid flow is critical for the efficient exploitation of shale resources and can be split into two stages: the flow in the artificial fractures and, more importantly, the flow from shale formations to the artificial fractures. In this study, X-ray diffraction, N2 adsorption, mercury intrusion, and ethylene glycol monoethyl ether adsorption were conducted on the shales collected from Es3middle, Es3lower, and Es4upper sub-members in the Dongying Sag to reveal the potential effects of the characteristics and prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 83 publications
(170 reference statements)
1
7
0
Order By: Relevance
“…The particle size (<3 mm) has been proven to be useful for obtaining the PSD by the combination of HPMI and N2GA by previous researchers. 15,51 Additionally, previous researchers also confirmed that the maximum extraction particle is limited to a millimeter level. 52 Therefore, we believe that the particle size of <3 mm can be applied to N2GA, HPMI, and Soxhlet extraction at the same time and may be more appropriate for the aim of this study.…”
Section: Geological Setting and Samplingmentioning
confidence: 73%
See 4 more Smart Citations
“…The particle size (<3 mm) has been proven to be useful for obtaining the PSD by the combination of HPMI and N2GA by previous researchers. 15,51 Additionally, previous researchers also confirmed that the maximum extraction particle is limited to a millimeter level. 52 Therefore, we believe that the particle size of <3 mm can be applied to N2GA, HPMI, and Soxhlet extraction at the same time and may be more appropriate for the aim of this study.…”
Section: Geological Setting and Samplingmentioning
confidence: 73%
“…Based on the discussions above, all samples were crushed to less than 3 mm , and extracted with dichloromethane solvent for at least 7 days to remove soluble organic matter by Soxhlet methods. Then, the sample was split into two aliquots.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations